2013
DOI: 10.2478/amsc-2013-0062
|View full text |Cite
|
Sign up to set email alerts
|

Application of Rough Set Theory for Choosing Optimal Location for Flotation Tailings Dump / Zastosowanie Teorii Zbiorów Przybliżonych Do Wyboru Optymalnej Lokalizacji Składowiska Odpadów Poflotacyjnych

Abstract: Flotation tailings dumps represent a potential threat to the environment. To corroborate this, numerous environmental disasters have occurred worldwide in the past. Pollution caused by breaking of tailings dump dams and overflowing of hazardous materials is still present, after several decades, and continue to threaten the environment. This paper presents a method for determining the most appropriate location for the flotation tailings dump using rough set theory. The review of the criteria that influence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They used six criteria for ranking six different locations. Štirbanovic et al [25] applied Rough Set From Figure 2, it can be concluded that MCDM is an actual research area and that the number of published articles has an upwards trend, as well as that MCDM methods are used to significant extent for solving problems in engineering (Figure 3).…”
Section: Application Of Mcdm In Mineral Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…They used six criteria for ranking six different locations. Štirbanovic et al [25] applied Rough Set From Figure 2, it can be concluded that MCDM is an actual research area and that the number of published articles has an upwards trend, as well as that MCDM methods are used to significant extent for solving problems in engineering (Figure 3).…”
Section: Application Of Mcdm In Mineral Processingmentioning
confidence: 99%
“…They used six criteria for ranking six different locations. Štirbanovic et al [25] applied Rough Set Theory (RST) for choosing the location for a flotation tailings dump. The evaluation of ten potential locations was carried out using nine criteria.…”
Section: Application Of Mcdm In Mineral Processingmentioning
confidence: 99%